Dinamika Konsep Welfare State di Indonesia : Antara Janji Konstitusi dan Kenyataan Ekonomi - Rizkyawan Hasan (Jurnal Hukum Lex Generalis, 2024)
The concept of welfare state is a concept that emphasizes the state's full role in all processes towards prosperity, welfare and ensuring equitable economic access to all citizens by prioritizing programs that support the implementation of guarantees for the fulfillment of citizens' rights. Indonesia as a country has also emphasized this through the constitution and various other regulations. These efforts can be realized by maximizing public services, assistance and protection through more participatory policies that are in accordance with the needs of the community. The purpose of this study is to analyze the dynamics of the concept of welfare state in Indonesia by identifying government programs and policies that have been regulated in the constitution. The results of this study conclude that the social programs and policies formulated today are still unable to overcome the problem of economic inequality experienced by the community. Economic growth that increases only shows economic improvement among the elite, people with middle to lower class economies still have to fight hard to get out of the poverty zone. Social policies through the PKH, BPNT, BPB, and BLT Food Risk Mitigation programs have not been effective and optimal. In fact, these programs often cause horizontal conflicts between communities. The state through the government should formulate social policies based on the developmental of the well-being of the people by relying on various facilities and authorities provided to support the process towards a prosperous country.